Accelerated fetal growth in early pregnancy and risk of severe large‐for‐gestational‐age and macrosomic infant: a cohort study in a low‐risk population. (20th August 2017) - Simic, Marija; Wikström, Anna‐Karin; Stephansson, Olof
Abstract: Introduction: Our objective was to examine the association between fetal growth in early pregnancy and risk of severe large‐for‐gestational‐age (LGA) and macrosomia at birth in a low‐risk population. Material and methods: Cohort study that included 68 771 women with non‐anomalous singleton pregnancies, without history of diabetes or hypertension, based on an electronic database on pregnancies and deliveries in Stockholm–Gotland Region, Sweden, 2008–2014. We performed multivariable logistic regression to estimate the association between accelerated fetal growth occurring in the first through early second trimester as measured by ultrasound and LGA and macrosomia at birth. Restricted analyses were performed in the groups without gestational diabetes and with normal body mass index (18.5–24.9 kg/m 2 ). Results: When adjusting for confounders, the odds of having a severely LGA or macrosomic infant were elevated in mothers with fetuses that were at least 7 days larger than expected as compared with mothers without age discrepancy at the second‐trimester scan (adjusted odds ratio 1.80; 95% CI 1.23–2.64 and adjusted odds ratio 2.15; 95% CI 1.55–2.98, respectively). Additionally, mothers without gestational diabetes and mothers with normal weight had an elevated risk of having a severely LGA or macrosomic infant when the age discrepancy by second‐trimester ultrasound was at least 7 days. Conclusions: In a low‐risk population, ultrasound‐estimated accelerated fetal growth in early pregnancy was associated with an increased risk of having a severely LGA or macrosomic infant.